Effect of xylose on the biological activity, physical property and antioxidant capacity of dried Aronia melanocarpa. Issue 5 (January 2021) - Sun, Wanting; Wang, Sai; Zhang, Jun; Sheng, Guihua; Wang, Meng; Chen, Xuanhong; Dong, Leichao; Zhou, Quancheng
Abstract: This research investigated effect of xylose on drying Aronia melanocarpa using response surface methodology (RSM) to produce the optimal drying conditions for high bioactive compounds. The conditions were drying temperature 58.70°C, drying time 8 h 48 min, and xylose solution concentration 50.70%. Subsequently, effects of drying conditions on physical properties of dried Aronia melanocarpa (DAM) were evaluated in Scanning electron microscope (SEM), Fourier transform infrared spectrum (FTIR), X-ray diffraction (XRD) and Different scanning calorimetry (DSC). The physical properties showed that DAM with xylose changed from amorphous to crystalline during drying process, which would extend the shelf life of DAM. Besides that, the physical properties results also showed that a Maillard reaction occurred during drying, which explained the improved antioxidant capacity of DAM with xylose. The results showed that xylose could reduce spoilage, prolong shelf-life of DAM, and indicated its use as a potential functional ingredients in the food industry.